Compaction and cementation controls on reservoir quality in Buntsandstein red beds - Schmidt, Christina (KIT Scientific Publishing, 2022)
Reservoir quality in fluvial siliciclastic rocks is variable. Permeability is influenced by micron-scale grain coatings or bedding style on the m-/km-scale. Outcrops allow the analysis of depositional environments and diagenesis, thus an investigation of reservoir quality controls. A process-oriented approach is used to understand variability in a meander deposit, compaction and cementation behavior of lithofacies types during burial and the discrepancy between porosity and permeability values.